A GIS method for volumetric assessments of erosion rills from digital surface models. (28th March 2019) - Báčová, Markéta; Krása, Josef; Devátý, Jan; Kavka, Petr
ABSTRACT: Modern non-contact methods for data acquisition are becoming widely used for monitoring soil erosion and for assessing soil degradation after rainfall events. Photogrammetric methods are especially favored to obtain a detailed and precise digital surface model (DSM) of the surveyed area. This paper introduces the algorithm and its Python implementation as a tool for ArcGIS software, which makes efficient automatic calculations of the volume of erosion rills or gullies. The input parameters are a DSM, and the rill edge polygon. The method was tested on an artificially created rill, where the result acquired using presented method was compared to the real volume. The comparison showed that the algorithm may underestimate the volume by 10–15%. In addition, the influence of the position of the rill edge polygon was tested on two DSMs of erosion rills. The resulting volumes of the rills, calculated on the basis of eight different edge polygons, varied by 5%. The algorithm also automates interpolation of the surface prior to erosion, which simplifies its usage in firstly monitored regions. The algorithm can also be used for volumetric analyses in other research areas and it is made available as a supplement of the publication.